Sacituzumab govitecan: breakthrough targeted therapy for triple-negative breast cancer. Issue 8 (3rd August 2019) - Weiss, Jennifer; Glode, Ashley; Messersmith, Wells A.; Diamond, Jennifer
ABSTRACT: Introduction : Triple negative breast cancer (TNBC) is an aggressive breast cancer subtype associated with an increased risk of recurrence and cancer-related death. Unlike hormone receptor-positive or HER2-positive breast cancers, there are limited targeted therapies available to treat TNBC and cytotoxic chemotherapy remains the mainstay of treatment. Sacituzumab govitecan (IMMU-132) is an antibody-drug conjugate targeting Trop-2 expressing cells and selectively delivering SN-38, an active metabolite of irinotecan. Areas covered : This review covers the mechanism of action, safety and efficacy of sacituzumab govitecan in patients with previously treated, metastatic TNBC. Additionally, efficacy data in other epithelial malignancies is included based on a PubMed search for 'sacituzumab govitecan' and 'clinical trial'. Expert opinion : Sacituzumab govitecan has promising anti-cancer activity in patients with metastatic TNBC previously treated with at least two prior lines of systemic therapy based on a single arm Phase I/II clinical trial. A confirmatory Phase III randomized clinical trial is ongoing. Sacituzumab govitecan has a manageable side effect profile, with the most common adverse events being nausea, neutropenia, and diarrhea. The activity of sacituzumab govitecan likely extends beyond TNBC with promising early efficacy data in many other epithelial cancers, including hormone receptor-positive breast cancer.